Model Kemitraan Berkelanjutan pada Usahatani Penangkaran Benih Padi di Desa Blimbing Kecamatan Sambirejo Kabupaten Sragen - Faiz Sabila Rosyada; Siti Nurlaela; Sukadi Sukadi; Annisa Wirrdiana Yuniasih (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Rice seed is considered one of the important elements in optimizing yields in rice cultivation. The increasing demand for certified rice seeds is one of the factors that facilitated the emergence of rice seed breeding partnerships between farmers and rice seed-producing companies. One of the partnerships to produce certified rice seeds is a partnership between PT Saprotan Benih Utama and the Rukun Tani Sulur Farmer Group. The partnership does not continue because there is no explicit agreement or contract farming between partner farmers and the company. This study aimed to determine the dynamics of partnerships and strategies for building partnerships to determine a sustainable partnership model in rice seed breeding farms. This research was conducted from January to June 2024 in Blimbing Village, Sambirejo District, Sragen Regency, Central Java Province. This research uses descriptive qualitative methods through in-depth interviews, observation, documentation, and focus group discussions. Data analysis uses the Miles and Huberman model, and partnership strategy was identified using SWOT analysis. The informants used in this study were seven people. The results showed that the rice seed breeding partnership dynamics that occurred between the Rukun Tani Sulur Farmer Group and PT Saprotan Benih Utama was in the form of an Agribusiness Operational Cooperation (KOA) pattern. Partner farmers provide land, inputs, and labor, while PT Saprotan Benih Utama provides costs and facilities. The strategy to build partnerships from the research results requires the application of SOPs and assistance to increase productivity and purchase price agreements for farmers. A written cooperation contract is needed to strengthen the partnership between farmers and companies so that both parties know their obligations and rights.